Mentoring perception and academic performance: an Academic Health Science Centre survey. Issue 1092 (18th March 2016) - Athanasiou, Thanos; Patel, Vanash; Garas, George; Ashrafian, Hutan; Shetty, Kunal; Sevdalis, Nick; Panzarasa, Pietro; Darzi, Ara; Paroutis, Sotirios
Abstract: Purpose: To determine the association between professors' self-perception of mentoring skills and their academic performance. Design: Two hundred and fifteen professors from Imperial College London, the first Academic Health Science Centre (AHSC) in the UK, were surveyed. The instrument adopted was the Mentorship Skills Self-Assessment Survey. Statement scores were aggregated to provide a score for each shared core, mentor-specific and mentee-specific skill. Univariate and multivariate regression analyses were used to evaluate their relationship with quantitative measures of academic performance (publications, citations and h-index). Results: There were 104 professors that responded (response rate 48%). There were no statistically significant negative correlations between any mentoring statement and any performance measure. In contrast, several mentoring survey items were positively correlated with academic performance. The total survey score for frequency of application of mentoring skills had a statistically significant positive association with number of publications (B=0.012, SE=0.004, p=0.006), as did the frequency of acquiring mentors with number of citations (B=1.572, SE=0.702, p=0.030). Building trust and managing risks had a statistically significant positive association with h-index (B=0.941, SE=0.460, p=0.047 and B=0.613, SE=0.287, p=0.038, respectively). Conclusions: This study supports the view that mentoring is associated with high academic performance. Importantly, it suggests that frequent use of mentoring skills and quality of mentoring have positive effects on academic performance. Formal mentoring programmes should be considered a fundamental part of all AHSCs' configuration.